Essential statistics for medical practice a case-study approach - Rees, D. G. (London ; New York : Chapman & Hall, 1994)
A firm understanding of the basic statistical methods used in current medical literature is now essential for medical practice as research papers have become increasingly statistical in nature. This book has a unique case-study approach starting with six actual research papers showing which statistical methods were used and how the results were obtained. It will enable the medical professional to understand the methods in an easy and accessible way. Essential Statistics for Medical Practice focuses on the most useful and commonly practised techniques and will therefore enable the reader to use the medical literature more knowledgeably and critically.
13. Sensitivity and specificity. 14. Study design. 15. Calculators and computers.
Includes bibliographical references and index.
All Ages.
Keywords: Medical statistics; Statistics -- Methods